Mobile Application to Improve Student Minimum Competency Assessment - Supandi, Supandi; Ariyanto, Lilik; Kusumaningsih, Widya; Aulia Firdaus, Anita (KnE Social Sciences, 2022)
This paper aims to assess whether understanding of the Minimum Competency Assessment (AKM) improves when taught to students through mobile learning. The research method was adapted from a development model whose stages consist of Analysis, Design, Development, Implementation, and Evaluation, but only carried out until the third stage (Development). Material experts and media experts carried out validation. The results show that the mobile application that has been developed was scored 87.88% in the ‘Very Good’ category by the media experts and was scored 89.62% in the ‘Very Good’ category by the material experts. Based on the results of data acquisition, it is shown that the mobile application is feasible to be used as a valid source to introduce students to AKM. Keywords: Media Development, Mobile Application, Minimum Competency Assesment